2023
DOI: 10.3390/geriatrics8010027
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Health Satisfaction in Spanish Physically Active Older Adults: A Cross-Sectional Observational Study

Abstract: Studies that analyze the predictors of satisfaction with the health of the elderly are scarce. That is the reason why the objective of this study is to analyze whether the physical-psychological state, sports practice, and the use of socio-health resources are factors that predict satisfaction with health status in physically active elderly people. The Physical Activity and Quality of Life questionnaires were applied to a sample of 397 elderly people in this cross-sectional observational study. The data have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The ability of daily living is closely related to the quality of life and health satisfaction of older individuals. Improving the physical ability of older adults can effectively prevent the development of physical diseases and positively impact their mental health, thereby reducing related health expenditures ( Parra-Rizo, 2018 ; Agustí et al, 2023 ). Comprehensive health management of older patients with chronic diseases should be strengthened ( Kim and Ha, 2020 ), and relevant policymakers should take measures to enhance the service capacity of primary medical and health institutions.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of daily living is closely related to the quality of life and health satisfaction of older individuals. Improving the physical ability of older adults can effectively prevent the development of physical diseases and positively impact their mental health, thereby reducing related health expenditures ( Parra-Rizo, 2018 ; Agustí et al, 2023 ). Comprehensive health management of older patients with chronic diseases should be strengthened ( Kim and Ha, 2020 ), and relevant policymakers should take measures to enhance the service capacity of primary medical and health institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the determinants influencing high satisfaction with health status is essential in the context of older people’s health. Key factors include maintaining functional abilities, absence of physical and psychological illnesses, adequate physical activity levels, regular use of health and social services, and satisfaction with the quality of these services ( Agustí et al, 2023 ). For older adults, significant aspects impacting quality of life are closely linked to health, interpersonal relationships, functional autonomy, and maintaining an active life.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have also revealed an association between cognitive impairments and muscular health issues (Chang, 2016), as well as a connection between poorer cognitive functioning and reduced gait speed and grip strength (Kan et al, 2013). Nevertheless, a deeper comprehension of the predictive capacity of overall cognitive functioning in relation to subjective health complaints is necessary, as the study by Agustı ´et al (2023) was able to identify, the absence of physical ailments, psychological clinical conditions, functional ability, engagement in physical activity and limited reliance on social and health services among older individuals can predict their level of satisfaction with their health.…”
Section: Introductionmentioning
confidence: 99%